Human motor transfer is determined by the scaling of size and accuracy of movement - Kwon, O. S.; Zelaznik, H. N.; Chiu, G.; Pizlo, Z. (Journal of Motor Behavior, 2011)
A transfer of training design was used to examine the role of the Index of Difficulty (ID) on transfer of learning in a sequential Fitts's law task. Specifically, the role of the ratio between the accuracy and size of movement (ID) in transfer was examined. Transfer of skilled movement is better when both the size and accuracy of movement are changed by the same factor (ID is constant) than when only size or accuracy is changed. The authors infer that the size-accuracy ratio is capturing the control strategies employed during practice and thus promotes efficient transfer. Furthermore, efficient transfer is not dependent on maintaining relative timing invariance and thus the authors provide further evidence that relative timing is not an essential feature of movement control.